Legal Nature of Public Fundrising - Piotrowski, Mariusz (Studia Oeconomica Posnaniensia, 2015)
The act of 14th March 2014 on public fundraising introduces the concept of authorized public fundraising, including the concept of public fundraising. The characteristic features of fundraising include the voluntary and selfless nature of contributors and the fact that contributions are passed to the fundraiser in cash or in kind . In the case of public fundraising there is a statutory, goal-oriented fundraising (remaining in the area of public functions). The assistance given by contributors are not donations, but neither can they be considered as unjust enrichment of the fundraiser.